2017
DOI: 10.1186/s40104-016-0137-1
|View full text |Cite
|
Sign up to set email alerts
|

Novel SNPs in IL-17F and IL-17A genes associated with somatic cell count in Chinese Holstein and Inner-Mongolia Sanhe cattle

Abstract: BackgroundBovine mastitis is the most common and costly disease of lactating cattle worldwide. Apart from milk somatic cell count (SCC) and somatic cell score (SCS), serum cytokines such as interleukin-17 (IL-17) and interleukin-4 (IL-4) may also be potential indicators for bovine mastitis. The present study was designed to investigate the effects of single nucleotide polymorphisms (SNPs) in bovine IL-17F and IL-17A genes on SCC, SCS and serum cytokines in Chinese Holstein and Inner-Mongolia Sanhe cattle, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
(22 reference statements)
0
12
0
Order By: Relevance
“…IL-17 plays a key role in the host defenses against bacterial and fungal infections [ 12 15 ]. Our recent work found that the mutations in IL-17 might serve as biomarkers for resistance against mastitis in Holstein cattle as well as Sanhe cattle, a dual purpose breed of China [ 16 ]. Moreover, IFN-γ is important for immune regulation as well as for the promotion of T cell priming and antibodies production [ 17 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL-17 plays a key role in the host defenses against bacterial and fungal infections [ 12 15 ]. Our recent work found that the mutations in IL-17 might serve as biomarkers for resistance against mastitis in Holstein cattle as well as Sanhe cattle, a dual purpose breed of China [ 16 ]. Moreover, IFN-γ is important for immune regulation as well as for the promotion of T cell priming and antibodies production [ 17 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serum was isolated from blood samples by incubating the samples at room temperature for 30 min followed by centrifugation at 3000× g for 10 min. The serum samples were then sent to Beijing Huaying Biological Technology Research Institute to evaluate serum biochemical assays of IL-4, IL-6, IL-10, IL-17, TNF-α, and IFN-γ using radioimmunoassay a technique, as described by Usman et al (2017) [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…The analysis of DEGs associated with inflammation and immunity indicated that the analyzed cows have a localized inflammatory reaction, which was consistent with the determination of SCC. In addition, Tahir Usman et al [40] found that interleukin 17F (IL-17F) and interleukin 17A (IL-17A) could be powerful candidate genes of mastitis resistance and the significant single nucleotide polymorphisms (SNPs) might be useful genetic markers against mastitis in both dairy and dual-purpose cattle. In this study, the expression levels of IL-17F and IL-17A did not change significantly.…”
Section: Discussionmentioning
confidence: 99%